Squats, squares, universities. About significant places in the biographies of rebels - Szczygieł, Przemysław (Adult Education Discourses, 2022)
This article discusses a fragment of an empirical study on the learning of adults participating in various forms of rebellion such as manifestations, demonstrations, urban activism and many others. Several interviewees from Spain pointed out the importance of specific places in their practices of rebellion and learning. These ‘significant places’ could be an important context of people’s lifelong learning. They mediate activities, build social relationships, produce norms, values and – what is crucial from the point of view of biographical research – construct the identities of rebels.